Adhesive Calculation System for Determination of Bonding Glue Needs Using Weighted Product and Lot Sizing Methods - Ita Purnamasari; Agus Setyawan; Ryan Naufal Hay’s (Universitas Serang Raya, 2019)
The production process that exists at PT. Parkland World Indonesia consists of several parts of the production process, one of which is the production process ofondonding which is used for shoe glue between outsole and upper. Adhesive is a material that is able to connect or unite the two surfaces of separate objects so that it has adequate strength when subjected to the load. This study discusses the making of an adhesive calculation system as a determination of the need for the first time to be ordered, using the weighted product method and lot sizing. The application was developed using the Power Builder programming language with Sybase SQL anyware as its database. With this system will help managers or superiors to know and determine alternative priorities or types of adhesive needs that must be prioritized for adhesive needs to help smooth the production process. To minimize the total cost of adhesive requirements.